Review of current status and ongoing reforms of the mental health system in Uzbekistan - Evgeniy Smekhov (BJPsych International)
Uzbekistan's mental health system is undergoing significant reform aimed at improving care and service delivery. This article provides a comprehensive evaluation of the current state of Uzbekistan's mental health system using the WHO 2010 monitoring and evaluation framework. It also details ongoing reforms designed to address systemic issues, enhance mental healthcare and ensure better health outcomes for the population.